2018
DOI: 10.15252/embj.201798311
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative proliferation of differentiated cells by mTORC 1‐dependent paligenosis

Abstract: In 1900, Adami speculated that a sequence of context-independent energetic and structural changes governed the reversion of differentiated cells to a proliferative, regenerative state. Accordingly, we show here that differentiated cells in diverse organs become proliferative via a shared program. Metaplasia-inducing injury caused both gastric chief and pancreatic acinar cells to decrease mTORC1 activity and massively upregulate lysosomes/autophagosomes; then increase damage associated metaplastic genes such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
176
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(196 citation statements)
references
References 75 publications
(153 reference statements)
17
176
0
3
Order By: Relevance
“…Cellular plasticity is induced in several tissues as part of the normal injury response (Merrell and Stanger, 2016; Tata and Rajagopal, 2016). Our data suggest that Mist1 + acinar cells also undergo cell type transitions in irradiated glands, consistent with reports documenting the plasticity of other differentiated secretory cells (Willet et al, 2018; Yu et al, 2018). This suggests that several cell populations have regenerative potential useful for restoring salivary gland function.…”
Section: Discussionsupporting
confidence: 92%
“…Cellular plasticity is induced in several tissues as part of the normal injury response (Merrell and Stanger, 2016; Tata and Rajagopal, 2016). Our data suggest that Mist1 + acinar cells also undergo cell type transitions in irradiated glands, consistent with reports documenting the plasticity of other differentiated secretory cells (Willet et al, 2018; Yu et al, 2018). This suggests that several cell populations have regenerative potential useful for restoring salivary gland function.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, Willet et al coined the term "paligenosis" to describe the process by which differentiated cells revert to a proliferative and regenerative state and undergo metaplasia in response to tissue injury in the context of stomach and pancreatic regeneration. 42 Our data suggest a similar process occurs in the context of fracture repair.…”
Section: Discussionsupporting
confidence: 62%
“…While one group has suggested that SPEM arises from isthmal progenitor cells in the corpus [57], the vast majority of evidence from multiple groups indicates that chief cells are indeed the predominant origin of SPEM lineages in the stomach corpus. [42,47,56,5860] Importantly, expression of pepsinogen I has been used as a marker of pseudopyloric metaplasia [61], consistent with the equivalence of pseudopyloric metaplasia with SPEM. Similarly, ductal metaplasia/PanIN lesions in the pancreas appear to evolve from reprogramming of zymogen-secreting pancreatic acinar cells [62].…”
Section: Lineage Origins Of Pyloric-type Reparative Mucous Cellsmentioning
confidence: 99%
“…SPEM appears to arise in the setting of parietal cell loss or acute corpus mucosal damage, primarily through transdifferentiation of chief cells into mucous cell metaplasia [42,47,56]. While one group has suggested that SPEM arises from isthmal progenitor cells in the corpus [57], the vast majority of evidence from multiple groups indicates that chief cells are indeed the predominant origin of SPEM lineages in the stomach corpus [42,47,56,[58][59][60]. Importantly, expression of pepsinogen I has been used as a marker of pseudopyloric metaplasia [61], consistent with the equivalence of pseudopyloric metaplasia with SPEM.…”
Section: Lineage Origins Of Pyloric-type Reparative Mucous Cellsmentioning
confidence: 99%